Head-to-Head Comparison of Urinary Hydroxyproline and Serum CTX-I in Monitoring Antiresorptive Therapy for Osteoporosis: A Network Meta-Analysis - Jonggara Octaviandra Siahaan; Eka Kurniawan (HM Publisher, 2025)
Background: Bone turnover markers (BTMs) are essential for monitoring the efficacy of antiresorptive therapies in osteoporosis. While serum C-terminal telopeptide of type I collagen (s-CTX-I) is the recommended reference marker for bone resorption, the utility of the classic marker, urinary hydroxyproline (u-HYP), in the modern therapeutic era remains debated. This study aimed to provide the first network meta-analysis (NMA) to compare the responsiveness of u-HYP and s-CTX-I to antiresorptive treatments. Methods: We conducted a systematic review and NMA of randomized controlled trials (RCTs) published between January 2015 and December 2024. We searched PubMed, Embase, and the Cochrane Central Register of Controlled Trials for RCTs of antiresorptive therapies (alendronate, denosumab, risedronate) in postmenopausal women with osteoporosis that reported changes in s-CTX-I or u-HYP at 3-6 months. A Bayesian random-effects NMA was performed to calculate the standardized mean difference (SMD) and rank the responsiveness of each marker. Results: Seven RCTs involving 3,451 patients met the inclusion criteria. The evidence network was well-connected for both markers. Antiresorptive therapies induced a significantly greater reduction in s-CTX-I levels compared to u-HYP. For instance, the effect of denosumab versus placebo was substantially larger when measured by s-CTX-I (SMD: -1.88; 95% Credible Interval [CrI]: -2.25 to -1.51) than by u-HYP (SMD: -0.95; 95% CrI: -1.22 to -0.68). Surface Under the Cumulative Ranking (SUCRA) analysis confirmed that s-CTX-I had a 98.2% probability of being the more responsive marker, compared to 1.8% for u-HYP. Heterogeneity was manageable, and no significant inconsistency was detected between direct and indirect evidence. Conclusion: This network meta-analysis provides robust, synthesized evidence that serum CTX-I demonstrates a markedly superior dynamic response to antiresorptive therapy compared to urinary hydroxyproline. These findings reinforce the position of s-CTX-I as the preferred biomarker for monitoring treatment efficacy in clinical practice.